2012
DOI: 10.1007/s11916-012-0272-0
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of Pain and Accompanying Symptoms during Cancer Treatment

Abstract: Patients' experience of cancer pain varies throughout the course of the disease. It is important to recognize that patients may experience more than one type of pain, and pain often occurs in the presence of other symptoms. Controlling pain requires a multi-faceted approach to assessing and treating the underlying mechanisms. This article reviews the pain mechanisms responsible for pain during cancer treatment and how expectations of pain and associated symptoms contribute to the pain experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…We found that post-operative pain was a stark complication of TAE. In this case, pain sensation could be attributed to the acute ischemia and necrosis of solid tumor, cell debris-induced inflammatory, and abnormal tissue tension [ 14 16 ]. To relieve pain, these patients are conventionally given oral nonsteroidal anti-inflammatory drugs (NSAID) or opioids [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that post-operative pain was a stark complication of TAE. In this case, pain sensation could be attributed to the acute ischemia and necrosis of solid tumor, cell debris-induced inflammatory, and abnormal tissue tension [ 14 16 ]. To relieve pain, these patients are conventionally given oral nonsteroidal anti-inflammatory drugs (NSAID) or opioids [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the options of using analgesics and other modalities, pain continues to be problematic in more than 50% of cancer patients (van den Beuken‐van Everdingen et al, ). Cancer pain is a multidimensional experience comprised of many factors, including distress and perceived control over pain, all of which affect the patient's functional status (Leung, Pachana, & McLaughlin, ; Schaller, Larsson, Lindblad, & Liedberg, ; Vallerand, Templin, Hasenau, & Riley‐Doucet, ; Wells, ; Wells & Sandlin, ). Although distress is experienced by all patients with cancer at some point during diagnosis and treatment (Hulbert‐Willams, Storey, & Wilson, ; National Comprehensive Cancer Network, ), in a study of ambulatory patients with cancer‐related pain, general symptom distress was found to be low, whereas, pain‐related distress was high (Vallerand, Templin et al, ).…”
Section: Introductionmentioning
confidence: 99%